Upaya Guru dalam Menumbuhkan Motivasi Belajar pada Siswa Tuna Grahita di SLB Samudra Terra Athena - Ridha Rahmah; Nova Estu Harsiwi (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study examines the teacher's efforts in fostering learning motivation in students with disabilities at SLB Samudra Terra Athena. This research uses a qualitative approach with descriptive methods, with data collection techniques through interviews, observation, and documentation during the research. The results showed that the strategies used by teachers in fostering learning motivation of students with intellectual disabilities include an individualized approach, the use of customized learning media, providing positive reinforcement, and building emotional closeness with students. These strategies are proven to increase students' engagement and interest in learning. This finding confirms the importance of teacher creativity in creating personalized and empathic learning approaches in special education.